Peran Save the Children dalam Perlindungan Hak Anak Pengungsi Rohingya di Bangladesh pada Fase Tanggap Darurat 2019 - 2023 - Annisa Syifa qulbiyah; Indrawati Indrawati (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The Rohingya humanitarian crisis in Bangladesh since the massive exodus in 2017 has placed refugee children as the group most vulnerable to human rights violations, particularly during the protracted emergency response phase. This study aims to analyze the role of the international non-governmental organization Save the Children in protecting the rights of Rohingya refugee children in Bangladesh during the 2019–2023 period. This research employed a qualitative method with a literature study approach, analyzing Save the Children's official documents, international agencies' reports, journal articles, and relevant policy publications. The analytical framework utilizes Lewis and Kanji's NGO Theory, which emphasizes the roles of service delivery, advocacy, and empowerment, alongside John Locke's Human Rights Theory, positioning children as subjects of natural rights to life, liberty, and property. The results indicate that Save the Children played a significant role in protecting the rights of Rohingya refugee children through direct service delivery such as health, nutrition, emergency education, and child-friendly spaces; policy advocacy for increased funding, educational access, and child protection; and empowering refugee communities through capacity building, child participation, and community-based protection mechanisms. Despite facing structural limitations and host country policy constraints, Save the Children's interventions contributed significantly to securing children's fundamental rights within a protracted humanitarian emergency. This study underscores the strategic role of international NGOs in addressing state limitations regarding trans-border refugee children's rights protection.